The Relationship Between Self-Esteem and Loneliness in Students at Makassar State University - Fiqran F, Andi Muhammad; Razak, Ahmad; Halima, Andi (Polteknik Ilmu Pemasyarakatan, 2025)
Students face various challenges in their educational process, students must be more independent in facing challenges in college. This study aims to determine the relationship between self-esteem and loneliness in students. The sampling technique used accidental sampling technique. This study uses a quantitative method with 151 research respondents. The measuring instrument used in this study is the Rosenberg's self-esteem scale with a reliability value of 0.908 and the UCLA (University of California, Los Angel) Loneliness Scale with a reliability value of 0.922. Hypothesis testing uses the Pearson correlation analysis technique using the SPSS version 25.0 application with a sig = 0.014 and r = -0.201. The results of this study indicate that there is a negative relationship between self-esteem and loneliness in students at Makassar State University, meaning that the lower the level of self-esteem, the higher the level of loneliness of students at Makassar State University. The implication of this study is that students are expected to be able to realize the importance of self-esteem as a buffer in socializing and are expected to reduce the level of loneliness they feel, and this study is expected to be able to contribute to the development of theories related to self-esteem and loneliness in students.